2020
DOI: 10.1136/bmjdrc-2020-001233
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metals and incident diabetes in midlife women: Study of Women’s Health Across the Nation (SWAN)

Abstract: IntroductionEnvironmental exposure to metals may play a role in the pathogenesis of diabetes; however, evidence from human studies is limited. We prospectively evaluated the associations of 20 urinary metal concentrations and their mixtures with incident diabetes in the Study of Women’s Health Across the Nation, a multisite, multiethnic cohort study of midlife women.Research design and methodsThe sample included 1237 white, black, Chinese and Japanese-American women, aged 45–56 years, free of diabetes at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 49 publications
2
38
1
Order By: Relevance
“…The results obtained at the conditions studied were consistent with previous literature; the increase in urinary excretion of Zn but not Cu has previously been described [ 38 ]. Mn excretion in diabetic conditions is controversial because some authors showed that this disease increased its excretion [ 5 , 39 ], whereas others found no significant changes [ 38 ]. The high food intake could be associated with a significant increase in net mineral absorption and retention ( Table 1 ).…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained at the conditions studied were consistent with previous literature; the increase in urinary excretion of Zn but not Cu has previously been described [ 38 ]. Mn excretion in diabetic conditions is controversial because some authors showed that this disease increased its excretion [ 5 , 39 ], whereas others found no significant changes [ 38 ]. The high food intake could be associated with a significant increase in net mineral absorption and retention ( Table 1 ).…”
Section: Discussionsupporting
confidence: 91%
“…A few prospective studies that explored the associations between metal exposure and diabetes mellitus presented the different roles of metals in diabetes mellitus development 15 , 17 , 25 , 26 , 27 , 28 , 29 , 30 . However, no unified conclusion about which metal is harmful, protective or irrelevant for diabetes mellitus has been achieved, partly because of the different metal mixture effects, implications of variable biological samples, times and levels of exposure in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although several recent studies have explored the relationship between multi‐metal exposure and diabetes mellitus risk, their conclusions are inconsistent. Several population‐based epidemiological surveys from different regions have found that magnesium (Mg), calcium (Ca), iron (Fe), zinc (Zn), arsenic (As), cadmium (Cd), copper (Cu) and lead (Pb) are associated with FBG or diabetes mellitus prevalence 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , whereas other studies have found no association 3 , 16 , 17 , 18 , 19 . Furthermore, the interaction of metals presents a challenge for correlation exploration.…”
Section: Introductionmentioning
confidence: 99%
“… 44 Another prospective study conducted in US women did not find a significant association between urinary W and incident diabetes; however, this study used above or below the limit of detection as exposed or unexposed, respectively, and only 29% of participants had detectable W levels. 21 Thus, the differences in exposure assessment could explain the discrepancies in results.…”
Section: Discussionmentioning
confidence: 99%